2022
DOI: 10.1186/s12877-022-03221-1
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of hip fractures in older adults residing in long-term care facilities with a hip airbag: a retrospective pilot study

Abstract: Background Hip and pelvic fractures do commonly occur among older adults. This pilot study aimed to evaluate the effect of introduction of the WOLK hip airbag on the incidence of hip fractures. Methods A retrospective study was performed among 969 participants residing within 11 long-term care facilities for older patients, belonging to one large healthcare organization in The Netherlands. The intervention concerned application of 45 WOLK hip-airba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In particular, our results show that by combining mathematically generated data with a limited amount of real data using transfer learning, the ability to forecast falls is increased significantly over that obtained with training using a small amount of available real data alone. Our approach resulted in a fall forecasting model that is 60%–70% reliable up to 2.35 s. This increase in forecasting times increases the time available for activating strategies to minimize the effects of a fall ( Nemeth et al, 2022 ; Márquez et al, 2023 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, our results show that by combining mathematically generated data with a limited amount of real data using transfer learning, the ability to forecast falls is increased significantly over that obtained with training using a small amount of available real data alone. Our approach resulted in a fall forecasting model that is 60%–70% reliable up to 2.35 s. This increase in forecasting times increases the time available for activating strategies to minimize the effects of a fall ( Nemeth et al, 2022 ; Márquez et al, 2023 ).…”
Section: Discussionmentioning
confidence: 98%
“…An important benchmark is how far in advance is it possible to forecast a fall? Clearly, the longer a fall can be forecasted ahead, the more time is available to activate strategies to mitigate the adverse effects of a fall ( Nemeth et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that the wrong figure appeared as Fig. 2 ; the figure should have appeared as shown below.…”
mentioning
confidence: 99%